Synaptic activity drives a genomic program that promotes a neuronal Warburg effect - Bas Orth, Carlos; Tan, Yan-Wei; Lau, David; Bading, Hilmar (The journal of biological chemistry, 2017)
Synaptic activity drives changes in gene expression to promote long lasting adaptations of neuronal structure and function. One example of such an adaptive response is the buildup of acquired neuroprotection, a synaptic activity- and gene transcription-mediated increase in the resistance of neurons against harmful conditions. A hallmark of acquired neuroprotection is the stabilization of mitochondrial structure and function. We therefore re-examined previously identified sets of synaptic activity-regulated genes to identify genes that are directly linked to mitochondrial function. In mouse and rat primary hippocampal cultures, synaptic activity caused an up-regulation of glycolytic genes and a concomitant down-regulation of genes required for oxidative phosphorylation, mitochondrial biogenesis, and maintenance. Changes in metabolic gene expression were induced by action potential bursting, but not by glutamate bath application activating extrasynaptic NMDA receptors. The specific and coordinate pattern of gene expression changes suggested that synaptic activity promotes a shift of neuronal energy metabolism from oxidative phosphorylation toward aerobic glycolysis, also known as the Warburg effect. The ability of neurons to up-regulate glycolysis has, however, been debated. We therefore used FACS sorting to show that, in mixed neuron glia co-cultures, activity-dependent regulation of metabolic gene expression occurred in neurons. Changes in gene expression were accompanied by changes in the phosphorylation-dependent regulation of the key metabolic enzyme, pyruvate dehydrogenase. Finally, increased synaptic activity caused an increase in the ratio of l-lactate production to oxygen consumption in primary hippocampal cultures. Based on these data we suggest the existence of a synaptic activity-mediated neuronal Warburg effect that may promote mitochondrial homeostasis and neuroprotection.